2017
DOI: 10.1093/mnrasl/slx102
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of the super-Eddington accretion on the quasar clustering

Abstract: Super-Eddington mass accretion has been suggested as an efficient mechanism to grow supermassive black holes (SMBHs). We investigate the imprint left by the radiative efficiency of the super-Eddington accretion process on the clustering of quasars using a new semi-analytic model of galaxy and quasar formation based on large-volume cosmological N -body simulations. Our model includes a simple model for the radiative efficiency of a quasar, which imitates the effect of photon trapping for a high mass accretion r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…∼ 10 8 − 10 9 yr (Volonteri 2010(Volonteri , 2012. Hence, under the assumption of a light-bulb light curve we have to invoke very massive initial seeds (M seed ∼ 10 9 M ), for which there is currently no theoretical foundation nor any potential progenitor objects known, or significantly super-Eddington accretion rates (Du et al 2015;Oogi However, there are several potential scenarios that could explain our findings. One option would be that the quasar has been growing for a much longer time than its lifetime estimate derived from the size of its proximity zone suggests, but it has been growing in a highly obscured phase, such that its ultraviolet (UV) radiation (and hence the ionizing continuum) has only "broken out" of this obscuring medium ∼ 10 4 yr ago (e.g.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…∼ 10 8 − 10 9 yr (Volonteri 2010(Volonteri , 2012. Hence, under the assumption of a light-bulb light curve we have to invoke very massive initial seeds (M seed ∼ 10 9 M ), for which there is currently no theoretical foundation nor any potential progenitor objects known, or significantly super-Eddington accretion rates (Du et al 2015;Oogi However, there are several potential scenarios that could explain our findings. One option would be that the quasar has been growing for a much longer time than its lifetime estimate derived from the size of its proximity zone suggests, but it has been growing in a highly obscured phase, such that its ultraviolet (UV) radiation (and hence the ionizing continuum) has only "broken out" of this obscuring medium ∼ 10 4 yr ago (e.g.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…This model originates from Nagashima & Yoshii (2004) and Nagashima et al (2005) (νGC model). Both νGC and ν 2 GC models have been used for a variety of astrophysical studies including gravitational waves, Lyα emitters, star formation, and AGN clustering (Enoki et al 2003;Enoki & Nagashima 2007;Kobayashi et al 2007;Makiya et al 2014;Oogi et al 2016Oogi et al , 2017. The SMBH growth and AGN properties in M16 are based on Enoki et al (2003), Enoki et al (2014), andShirakata et al (2015).…”
Section: Model Descriptionsmentioning
confidence: 99%
“…Volonteri & Natarajan 2009;Shirakata et al 2016), and AGN clustering (e.g. Fanidakis et al 2013;Oogi et al 2016Oogi et al , 2017.…”
mentioning
confidence: 99%
“…Abramowicz et al 1988;Watarai et al 2000;Mineshige et al 2000). Oogi et al (2017) have found that this limitation of the bolometric luminosity has a large impact on the clustering signal of the resultant mock AGN population. To include this effect, we adopt the following relation as the bolometric luminosity normalised by the Eddington luminosity, λ Edd ≡ L bol /L Edd :…”
Section: Agn Activitymentioning
confidence: 99%